Integrasi Laboratorium Virtual dalam Perkuliahan LPTK: Membangun Kompetensi TPACK Calon Guru Sains - Gunawan Gunawan; Baiq Nabila Saufika Zainuri (Indonesian Publication Center, 2022)
Digital transformation in Teacher Training Institutions (LPTK) demands the preparation of pre-service science teachers who master Technological Pedagogical Content Knowledge (TPACK). This integrative review aims to analyze the developmental trends of virtual laboratory technology and formulate strategies for its enhancement in building the TPACK competency dimensions of pre-service science teachers. Following the PRISMA protocol, a comprehensive literature search was conducted across Scopus, DOAJ, Crossref, and Google Scholar databases. The results of the thematic synthesis indicate that the evolution of virtual laboratory technology shapes Technological Knowledge (TK), while real-time data visualization strengthens the Content Knowledge (CK) of pre-service teachers. Furthermore, open-ended sandbox environment designs stimulate Pedagogical Knowledge (PK) through the formulation of systematic scaffolding to address students' diverse initial academic abilities. Holistic TPACK integration is achieved when simulation technology is synergized into a blended learning model as a cognitive-friendly pre-practicum bridge. This review offers substantial implications for LPTK lecturers in designing digital practicum curricula capable of mitigating extraneous cognitive load.